Islamic Educational Thinking Of Syed Muhammad Naquib Al-Attas And Its Relevance To The Moral Crisis Of Youth - Zuhro Dwi Mahmudah; Vita Firdausiyah; Abd. Hanan (-, 2026)
This study aims to analyze the Islamic educational thought of Syed Muhammad Naquib al-Attas and examine its relevance to the moral crisis of youth in the modern era. The rapid development of the digital era has significantly influenced adolescents’ lifestyles, ways of thinking, and behavior, resulting in various forms of moral degradation such as declining adab, weakening spiritual values, deviant behavior, and identity crises. This study employs a qualitative approach using library research as the research design. Data were collected through documentation studies by examining various primary and secondary sources related to Syed Muhammad Naquib al-Attas’s educational thought, the concept of ta’dib, Islamic education, and youth moral crises. The data were analyzed using content analysis methods to understand, interpret, and draw conclusions from the examined literature. The findings reveal that the concept of adab in Al-Attas’s educational thought occupies a central position in shaping knowledgeable and moral individuals. The moral crisis among youth is essentially caused not only by weak social control but also by an epistemological crisis that leads to the loss of the ability to understand the true nature of knowledge and values. The concept of ta’dib proposed by Al-Attas serves as an important solution because it emphasizes not merely behavioral formation, but also the transformation of consciousness, the integration of knowledge and values, and the development of morality oriented toward truth and spiritual responsibility. Therefore, strengthening adab in Islamic education becomes a fundamental agenda for shaping a young generation with noble character, strong morality, and the ability to face the challenges of modernity.